The Effect of Eye Exercises of Acupoints on Myopia Progression: A 3-Year Cohort Report from the Beijing Myopia Progression Study - Liang YB; Vasudevan B; Lin Z; Zhou HJ; Ciuffreda KJ (Dove Medical Press, 2020)
Yuan Bo Liang,1,2 Balamurali Vasudevan,3 Zhong Lin,1,2 Hong Jia Zhou,1,2 Kenneth J Ciuffreda4 1Eye Hospital and School of Ophthalmology and Optometry, Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 2National Clinical Research Center for Ocular Diseases, Wenzhou, Zhejiang, People’s Republic of China; 3College of Optometry, Mid Western University, Glendale, AZ, USA; 4Department of Biological and Vision Sciences, SUNY College of Optometry, New York, NY, USACorrespondence: Zhong LinPhDEye Hospital and School of Ophthalmology and Optometry, Wenzhou Medical University, No. 270 West College Road, Wenzhou, Zhejiang 325027, People’s Republic of ChinaTel +86-577-88824116Email linzhong_@126.comPurpose: To investigate the impact of eye exercises of acupoints on myopic progression among Chinese urban students.Methods: The Beijing Myopia Progression Study (BMPS) was a three-year cohort study, with 386 students (aged 6– 17 years) enrolled at baseline. These students were invited to be reexamined in the years 2011, 2012, and 2013. The student’s cycloplegic refraction at each visit and the parental non-cycloplegic refraction at baseline were performed. Students were also required to complete the eye exercise of acupoints questionnaire and the convergence insufficiency symptom survey (CISS).Results: At the final follow-up, 226 students (57.2%) with complete refraction and eye exercises questionnaire data were enrolled in the present study. In the multivariate analysis, only students who performed the eye exercises twice or more per day had less myopic refractive change (β=0.32, p=0.04), as compared to those who performed the eye exercises less than twice per day. No significant association was found between the CISS score and the refractive change for items in the eye exercises questionnaire.Conclusion: In this study cohort, the Chinese eye exercises of acupoints had a modest effect on reducing myopic progression among Chinese urban students aged 6 to 17 years. The precise mechanism remains unclear, especially in the absence of a control group.Keywords: eye exercises, acupoints, myopia, progression, myopia risk factors, convergence insufficiency symptom survey